Boron and nitrogen co-doped porous carbon nanospheres for oxidative dehydrogenation of ethane to ethylene. (September 2022) - Cao, Xueyu; Wu, Xinyu; Liu, Yong; Geng, Haojie; Yu, Siyu; Liu, Shetian
Abstract: Boron and nitrogen co-doped carbon nanospheres (BX CN) were fabricated using graphitic carbon nitride (g-C3 N4 ) as the precursor and the nitrogen source, and boric acid as the boron source. They featured high specific surface area and porous structure. Besides, the doping of B brought improved chemical and thermal stability of the material. They were further used as catalysts for the oxidative dehydrogenation of ethane (ODHE) for the first time. The BX CN demonstrated higher conversion of ethane and higher selectivity towards ethylene, compared with other carbon catalysts such as carbon nanotubes reported in literature. An ethane conversion of 15.8% with a selectivity of 56.0% towards ethylene were achieved on B0 · 1 CN at a reaction temperature of 525 °C. The B0 · 1 CN showed an excellent stability within 7 h ODHE test at 450 °C. This work offers a new strategy of using heteroatoms co-doped carbon-based catalysts with improved activity for ODHE under lower temperatures. Graphical abstract: Image 1